Spectral Reflectance (350–2500 nm) Properties of Historic Artists' Pigments. II. Red–Orange–Yellow Chromates, Jarosites, Organics, Lead(–Tin) Oxides, Sulphides, Nitrites and Antimonates. Issue 2 (April 2016) - Cloutis, Edward; Norman, Leif; Cuddy, Matthew; Mann, Paul
Unprocessed and minimally processed earth materials have been the traditional source of artist's pigments, dating back to prehistory. Identifying pigments comprising a cultural artefact has important conservational, scholarly and historic applications. In this study, we focus on red–orange–yellow historic artists' pigments that are not coloured by iron oxyhydroxides; specifically chromates, jarosites, organics, oxides, sulphides, nitrites and antimonates. We searched for specific spectroscopic characteristics that can be applied to their identification and differentiation from other pigments, with an emphasis on the less well studied near infrared region ( ca 1000–2500 nm). We combined and compared reflectance spectroscopy (350–2500 nm) with X-ray diffractometry for this purpose. It was found that these two analytical techniques are often complementary. Chromate, lead oxide, lead–tin oxide, lead antimonate and sulphide reflectance spectra are characterised by an absorption edge in the visible region as their only or main diagnostic spectral characteristic. While this pigment grouping can be recognised by the lack of additional spectral features, the presence of organic binders adds additional spectral features that can complicate their identification. Other techniques, such as Raman or infrared spectroscopy, are better suited for their non-destructive identification. Organic-derived pigments also exhibit an absorption edge but with additional spectral features that may allow for their unique identification. However, all pigment identifications can be complicated by absorption features associated with organic binders. Yellow earths which derive their colour from the mineral jarosite possess multiple diagnostic absorption bands that can be used for their unique identification. Cobalt yellow possesses minor absorption bands in the 2400–2500 nm region that may allow for its unique identification.